2023
DOI: 10.1101/2023.03.15.23286981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 and effects of booster vaccination with BNT162b2 on six-month long COVID symptoms, quality of life, work productivity and activity impairment during Omicron

Abstract: Background: Longitudinal estimates of long COVID burden during Omicron remain limited. This study characterized long-term impacts of COVID-19 and booster vaccination on symptoms, Health-Related Quality of Life (HRQoL), and Work Productivity Activity Impairment (WPAI). Methods: Outpatients with ≥1 self-reported symptom and positive SARS-CoV-2 test at CVS Health United States test sites were recruited between 01/31-04/30/2022. Symptoms,EQ-5D and WPAI were collected via online surveys until 6 months following inf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This analysis supports earlier work that found that the BNT162b2 booster could reduce the risk and burden of PASC (Di Fusco et al 2023). Boosted participants reported fewer and less durable symptoms and vaccination was associated with lower latent symptom burden class, increased quality of life, and decreased activity impairment (Di Fusco et al 2023).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This analysis supports earlier work that found that the BNT162b2 booster could reduce the risk and burden of PASC (Di Fusco et al 2023). Boosted participants reported fewer and less durable symptoms and vaccination was associated with lower latent symptom burden class, increased quality of life, and decreased activity impairment (Di Fusco et al 2023).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is relevant to the question of how long SARS-CoV-2 vaccines may be protective (Tenforde, Link-Gelles, and Patel 2022), considering the subjects’ most recent vaccination may be months old prior to enrollment in our study. As previously reported, individuals in the primary vaccine group were vaccinated up to 11 months before the study (Di Fusco et al 2023). In the more recently available booster group, some were boosted up to 4 months before the study (Di Fusco et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations